Character Education Strategy In Improving Student Discipline At Islamic State University Higher Education Mahmud Yunus Batusangkar - Rahayu Eka Putri (Yayasan Adra Karima Hubbi, 2023)
The vulnerability of knowledge about discipline in the world of education today is the result of a lack of respect for others. Therefore, it is necessary to instill character education to make improvements in students so that it becomes a form of disciplined assessment of character formation in the educational environment. The role of character improvement in education is the aim of the author's research to analyze the extent to which character is implemented as a form of improving moral discipline among Islamic State University Higher Education Mahmud Yunus Batusangkar students. This research is a type of qualitative descriptive research with data collection taken from field observations carried out by researchers regarding the 3 option assessments observed and interview techniques. From the results of the research, it was found that the application of the options observed was able to provide increased discipline in students. The results of this observation were also supported by an interview process which provided views on whether the application of student character was able to instill discipline towards others. Therefore, the conclusion in this research is that it is able to provide an allocation if Islamic State University Higher Education Mahmud Yunus Batusangkar students have implemented maximum character education, thereby creating students who have moral character and high discipline